The Implementation of Artificial Intelligence (AI) in Effective and Accurate Strategic Decision-Making in Higher Education Environments - Mulyono, Mulyono; Saidah, Safura (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2026)
The increasingly complex higher education environment demands a more effective and accurate data-driven strategic decision-making approach. This study aims to analyze the implementation of Artificial Intelligence (AI) in supporting the effectiveness and accuracy of strategic decision-making in the higher education environment. This article uses a literature review approach with descriptive analysis methods. This approach was conducted by collecting, analyzing, and synthesizing various scientific literature related to the application of Artificial Intelligence (AI) in supporting the effectiveness and accuracy of strategic decision-making in higher education environments. The results show that the implementation of AI, although still in its early stages, has significantly improved predictive accuracy and objectivity in various strategic areas, such as 1) student recruitment; 2) student retention; 5), and resource allocation. Qualitative findings reveal that AI acts as a powerful decision support system. However, the main challenges are non-technical in nature, namely: 1) data quality and availability, 2) lack of expert human resources, and 3) organizational cultural resistance. Based on these findings, the researchers recommend that in order to maximize the benefits of Artificial Intelligence (AI) in strategic decision-making effectively and accurately, universities need to invest in data infrastructure, human resource capacity, and ethical policies, while ensuring that human leadership remains the final decision-maker that considers the values and context of the institution.